2012
DOI: 10.3171/2012.9.spine111026
|View full text |Cite
|
Sign up to set email alerts
|

Posterior vertebral column resection for correction of rigid spinal deformity curves greater than 100°

Abstract: Object The surgical treatment of severe and rigid spinal deformities poses difficulties and dangers. In this article, the authors summarize their surgical techniques and evaluate patient outcomes after performing posterior vertebral column resection (PVCR) for the correction of spinal deformities with curves greater than 100°, and investigate the crucial points to ensure neurological safety during this challenging procedure. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 31 publications
3
58
0
3
Order By: Relevance
“…5 , 8 , 9 Complications in patients who were treated by VCR for scoliosis have ranged from 17.9% to 40.3%. [16][17][18] In our study, the complication rate was 23.8%, which is similar to the 2 procedures taken separately. We therefore conclude that spine-shortening osteotomy is a safe alternative to traditional strategies for the treatment of congenital scoliosis associated with tethered cord.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…5 , 8 , 9 Complications in patients who were treated by VCR for scoliosis have ranged from 17.9% to 40.3%. [16][17][18] In our study, the complication rate was 23.8%, which is similar to the 2 procedures taken separately. We therefore conclude that spine-shortening osteotomy is a safe alternative to traditional strategies for the treatment of congenital scoliosis associated with tethered cord.…”
Section: Discussionsupporting
confidence: 82%
“…without a tethered cord. [16][17][18] In addition, we found that the sagittal vertical axis was around 1.4 ± 0.9 cm before surgery. It remained stable after surgery at 1.3 ± 0.8 cm at the immediate postoperative assessment and 1.2 ± 1.0 cm at the last follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Seven studies were excluded for insufficient number of patients (less than 10 patients) and one study was excluded due to the fact that the ''modified PVCR'' was performed. Seventeen studies from seven institutions [7,[9][10][11][13][14][15][16][17][18][19][20][21][22][23][24][25] were included for further analysis. To avoid overlap of patients in different studies, only one main publication from each institution was retained.…”
Section: Resultsmentioning
confidence: 99%
“…In our experience, this technique creates a space for spinal correction and spinal cord tension adjustment, and the correction can be performed under direct inspection and by palpation of the tension in the spinal cord through the space. 26 During the procedure, the focus of the correction process is on the spinal cord, which is protected from excessive tension and stretching by the shortening of the spinal column. Following posterior vertebral column resection, the tension of the spinal cord at the craniocervical junction was decreased in our patients, and abnormal CSF flow was indirectly improved.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was performed as previously reported 26 and included resection of the os seous elements posterior and anterior to one or more spinal segments as well as the upper and lower vertebral discs adjacent to the segments. This created sufficient space in which correction and reconstruction could be performed.…”
Section: Posterior Vertebral Column Resectionmentioning
confidence: 99%